ANTI-INFLAMMATORY STUDIES OF NOVEL METHYL AMINO AND HYDRAZINO BENZIMIDAZOLES ON CARRAGEENANINDUCED PAW EDEM IN RATS - KUNNAMBATH KRISHNAKUMAR; ANILCHANDRA RAMAKANT BHAT; KUPPUSWAMY UMAA (International Journal of Pharma and Bio Sciences, 2013)
A series of N’, N’’-[1-(1H-benzimidazole-2-yl)-2-(4-substituted phenyl ethane-1, 2-diyl)] substituted aromatic amines (AK1- AK6) and hydrazides (AKH6 – AKH11) were synthesized by treating 2-methyl benzimidazole with different substituted aromatic aldehydes in the presence of ethanol to produce 2-[2-(4 chlorophenyl)-vinyl]-1H-benzimidazole. It was brominated to 2-[1, 2 dibromo 2-(4-substituted phenyl) ethyl]-1H-benzimidazole, which on treatment with different substituted amines and hydrazides in absolute alcohol brings forth the newer compounds. The structures attributed to the newly synthesized compounds were elucidated using IR, NMR, MASS techniques besides elemental analysis. The compounds were evaluated for their anti-inflammatory potentials by carrageenan induced paw edema bio-assay in rats. Many of the target compounds showed good anti-inflammatory activity. A most distinctive derivative, 1-[1-H-benzimidazol-2-yl]-N, N’,2-tris (4-chlorophenyl)-ethane-1,2-diamine (AK5) was identified in the present study, due to its remarkable anti-inflammatory potentials and was found to be equipotent with that of Indomethacin, observed after the introduction of p-chloro anilino group with 2- methyl benzimidazole moiety. The acute toxicity study of the compounds indicated that they were well tolerated. Therefore, such a compound would represent a fruitful matrix for the development of anti-inflammatory candidates.